Prevalence of polypharmacy in heart failure patients: A retrospective cross-sectional study in a tertiary hospital in Saudi Arabia - Mohammed M. Alsultan; Rabab Alamer; Fatimah Alammar; Wafa Alzlaiq; Abdullah K. Alahmari; Ziyad S. Almalki; Faisal Alqarni; Dhfer M. Alshayban; Fawaz M. Alotaibi; Ibrahim M. Asiri; Fahad Alsultan; Sawsan M. Kurdi; et al. (Elsevier, 2023)
Background: Cardiovascular disease is the leading cause of death and disability worldwide. It is a general term used to describe a group of disorders that affect the heart or blood vessels. This study aimed to evaluate the prevalence and predictors of polypharmacy in patients with heart failure. Methods: We conducted a cross-sectional study in a tertiary hospital in Saudi Arabia. Data was extracted from an electronic database between January 2019, and December 2022. The study included all adult patients with heart failure who visited outpatient clinics; individuals with cancer were excluded. The outcome variable in our study was "polypharmacy" which was defined as the use of eight or more medications. Descriptive analysis was performed using frequencies and percentages for categorical variables. In addition, Multivariate logistic regression was used to assess the covariates associated with polypharmacy. Results: A total of 331 patients with heart failure were included in this study. The prevalence of polypharmacy among our HF population was 39.88 %. Most participants were male (60.73 %), and 60 years or older (68 %). The most frequently used medications were beta-blockers (67.98 %) and diuretics (58.31 %), whereas the least frequently used medications were hydralazine and histamine H2 blockers (5.74, and 3.02 %, respectively). Polypharmacy was likely to be a non-significantly higher in individuals aged between 60 and 69 years (adjusted odds ratio (AOR) = 1.52; 95 % confidence interval (CI) 0.78-2.98) and suffering from hypertension (AOR = 1.48; 95 % CI 0.83-2.64). However, patients with heart failure and diabetes mellitus had a significant six-fold higher of polypharmacy than those without diabetes mellitus (AOR = 6.55; 95 % CI 3.71-11.56). Conclusion: Patients with heart failure often use multiple medications. Patients with heart failure together with diabetes have a higher risk of polypharmacy. Therefore, healthcare professionals should manage polypharmacy to improve the outcomes in patients with heart failure.